Implementing Character Values to Learners in Didikan Subuh Program - Sultanik, Dewa; Japeri, Japeri; Taufan, Muhammad; Efendi, Efendi (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2022)
This study aims to determine whether character values can be instilled in students through the dawn education program. This study uses a combined method of qualitative and quantitative (explanatory mixed method design). Qualitative data sources were taken from four informants through in-depth interviews who were selected using purposive sampling. While quantitative data was taken to fifty-four students who were selected using simple random sampling technique. Interview data with informants were analyzed thematically using four steps (data collection, data reduction, data presentation and conclusion drawing). Furthermore, quantitative data were analyzed descriptively using SPSS 21. Overall, the results of the analysis of the two stages of this study showed that there were fifteen character values in the dawn education program for students. The fifteen character values are: i) religious, ii) discipline, iii) self-confidence, iv) hard work, v) cooperation, vi) responsibility, vii) honesty, viii) courtesy, ix) tolerance, x) independent, xi) curiosity, xii) friendly, xiii) peace-loving, xiv) environmental care, and xv) social care. The results of the study have also proven that dawn education activities can be well implemented for the character education of students.